ANALISA BEBAN TIDAK SEIMBANG DAN KONSERVASI ENERGI PADA UTILITAS MOTOR LISTRIK DI INDUSTRI FARMASI (Studi Kasus : PT. XZY, tbk) - Bambang Supradono; Achmad Solichan (MEDIA ELEKTRIKA, 2011)
Use of utility electric motor in an industry become is a basic requirement, electric motor serves as a means of supporting drivers / mechanics of a tool such as pumps, chillers, conveyors etc. The electric motor takes energy consumption in the world's greatest industrial and motors is expected to use about 70% of the total electrical load in the industry. This research aims to analyze unbalanced load on electric motor and how to solve that problems. Unnecessary consumption of energy from the electric motor is usually caused inefficiencies and unbalanced load burden. For that we need ways to makeconservation / energy saving programs.Keywords: electric motor, inefficiency load, unbalanced load, energy conservation